Modeling a small-scale test rig of quarter car railway vehicle suspension system - Ahmed, Md. Iqbal; Md. Yusof, Hazlina; Rashid, Muhammad Mahbubur (University of Derby, 2015)
Suspension system is a mechanism which isolates the vehicle body from road shocks and unwanted vibrations. A basic suspension system usually consists of spring, damper, rods, and ball joints in both automotive and railway transportation. The primary aim of this project is to design and develop a small-scale test rig of quarter car railway vehicle suspension system. This paper describes component selection strategy, technical design procedure, and research investigation of test rig and suspension system. The rig design and motion analysis is conducted by using Solidworks motion study tool where dynamic characteristic of the system, such as, required torque, acceleration and displacement of vehicle body and bogie are investigated based on selected parameters and track inputs.